Enhancing Diagnostic Precision: The Role of Specialized Head Coil MRI in Disc Displacement Diagnosis of Temporomandibular Joint - Latief, Shofiyah; Murtala, Bachtiar; Thalib, Bahruddin; Muis, Mirna; Ilyas, Muhammad; Ruslin, Muhammad; Utama, Dharma; Bahar, Burhanuddin (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: This study discusses the use of coil heads in Magnetic Resonance Imaging (MRI) technology to diagnose Temporomandibular Joint Disc Dislocation (TMJ). TMJ disc dislocation is a common condition of the temporomandibular joint that can hurt a person's jaw and make it difficult for them to open their mouth fully. This study sought to assess the effectiveness of MRI with coil heads performed in locating and diagnosing TMJ disc dislocations. Method: Analytic observational with cross-sectional design. A diagnostic test to assess the validity of MRI. Predictor analysis was performed using a multivariate logistic regression test. Result: This study shows disparities in the findings of MRI and RDC tests for detecting temporomandibular joint disc dislocations. Clinical complaints have a strong correlation with disc displacement on MRI and RDC. In the MRI, disc dislocation was significantly correlated with all panoramic examination factors. Only the impaction variable in RDC significantly influences disc dislocation. Asymmetrical condyle position on panoramic inspection and complaints present for more than a year on physical examination indicate disc dislocation. These findings imply that MRI is more effective at identifying displaced temporomandibular joint discs, leading to a more precise diagnosis. Conclusion: The diagnosis of TMJ disc dislocations often involves MRI with coil heads. Medical practitioners can more easily spot disc abnormalities or changes in position thanks to this technology, which offers an accurate and thorough image of the temporomandibular joint's anatomy